Outcomes of endoscopic submucosal dissection for superficial esophageal cancer in an elderly population: a retrospective single center cohort study - Iizuka, Toshiro; Kikuchi, Daisuke; Hoteya, Shu (Endoscopy International Open, 2019)
Background and study aims Endoscopic submucosal dissection (ESD) is increasingly being used to treat superficial esophageal cancer in the elderly. However, data on clinical outcomes in this age group are limited. The aim of this study was to evaluate the safety and efficacy of ESD in treatment of superficial esophageal cancer and its effect on long-term outcome in the elderly.Patients and methods In total, 664 consecutive patients with a histological diagnosis of squamous cell carcinoma or high-grade intraepithelial neoplasia who underwent ESD between April 2008 and March 2016 at our institution were enrolled. Clinical outcomes and prognostic factors were compared retrospectively between those aged 75 years or older (n = 162) and those aged younger than 75 years (n = 502).Results There was no significant difference in post-ESD bleeding (0 vs. 0.8 %, P = 0.27) and perforation rates (1.8 vs. 1.2 %, P = 0.47) between the two age groups; however, stricture rate was higher in younger patients than in elderly patients (20.8 % vs 11 %; P = 0.036). There was no significant difference in the rate of locoregional recurrence between the two groups. Overall survival was significantly different between the two groups, but cause-specific survival was similar.Conclusion These findings confirm the efficacy of ESD for superficial esophageal cancer in selected elderly patients (75 years or older) who were fit for the treatment because they can achieve similar long-term survival to younger patients.